Extensive Corrective Fixation Surgeries for Adult Spinal Deformity Improve Posture and Lower Extremity Kinematics During Gait. Issue 19 (1st October 2017) - Arima, Hideyuki; Yamato, Yu; Hasegawa, Tomohiko; Kobayashi, Sho; Yoshida, Go; Yasuda, Tatsuya; Banno, Tomohiro; Oe, Shin; Mihara, Yuki; Togawa, Daisuke; Matsuyama, Yukihiro
Abstract : Study Design: Longitudinal cohort. Objective: The present study aimed to document changes in posture and lower extremity kinematics during gait in patients with adult spinal deformity (ASD) after extensive corrective surgery. Summary of Background Data: Standing radiographic parameters are typically used to evaluate patients with ASD. Previously, preoperative walking and standing posture discrepancy were reported in patients with ASD. We did not include comparison between before and after surgery. Therefore, we thought that pre- and postoperative evaluations for patients with ASD should include gait analysis. Methods: Thirty-nine patients with ASD (5 men, 34 women; mean age, 71.0 ± 6.1) who underwent posterior corrective fixation surgeries from the thoracic spine to the pelvis were included. A 4-m walk was recorded and analyzed. Sagittal balance while walking was calculated as the angle between the plumb line on the side and the line connecting the greater trochanter and pinna while walking ( i.e., the gait-trunk tilt angle [GTA]). We measured maximum knee extension angle during one gait cycle, step length (cm), and walking speed (m/min). Radiographic parameters were also measured. Results: The mean GTA and the mean maximum knee extension angle significantly improved from 13.4° to 6.4°, and −13.3° to −9.4°( P  < 0.001 and P  = 0.006), respectively. The mean step length improved from 40.4 to 43.1 cm ( P  = 0.049), but there was no significant change in walking speed (38.4 to 41.5 m/min, P  = 0.105). Postoperative GTA, maximum knee extension angle and step length correlated with postoperative pelvic incidence minus lumbar lordosis ( r  = 0.324, P  = 0.044; r  = −0.317, P  = 0.049; r  = −0.416, P  = 0.008, respectively). Conclusion: Our results suggest that postoperative posture, maximum knee extension angle, and step length during gait in patients with ASD improved corresponding to how much correction of the sagittal spinal deformity was achieved. Level of Evidence : 3